Insider threat behavior factors: a comparison of theory with reported incidents - Munshi, A.; Dell, Peter; Armstrong, Colin (The Institute of Electrial and Electronics Engineers, Inc, 2012)
Almost all organizations and sectors are currently faced with the problem of insider threats to vital computer assets. Internal incidents can cause more than just financial losses; the costs can also include loss of clients and damage to an organization’s reputation. Substantial academic research investigating internal threats has been conducted. This paper examines a number of theoretical models drawn from academic literature to identify a set of factors that are thought to be behavior factors associated with insider threats. These factors are then critiqued using empirical evidence from reported incidents, resulting in insights into areas where the theoretical perspectives of academic literature are both supported and unsupported by actual case evidence. The paper concludes with recommendations for future research directions for academic researchers.